Incredible PCE enhancement induced by damaged perovskite layers: deeply understanding the working principle of additives in bulk heterojunction perovskite solar cells. Issue 10 (16th February 2018) - Gao, Liguo; Wang, Likun; Ding, Xiaogang; Zhao, Erling; Yang, Shuzhang; Zhao, Yingyuan; Li, Yanqiang; Wang, Shufeng; Ma, Tingli
Abstract : New work principle of additives in bulk heterojunction PSCs (BHJ-PSCs) were proposed by self-designed experiment, where crystallization of perovskite layer was hampered and recombination risk increased. Abstract : The power conversion efficiency (PCE) of perovskite solar cells (PSCs) can be improved by introducing appropriate additives into perovskite precursor solutions. However, the exact role and mechanism of additives are still unclear. In this study, self-designed cognition experiments were conducted to improve the hole extraction efficiency, as well as to deeply understand the working principle of additives. A common hole transport material, 2, 2′, 7, 7′-tetrakis[ N, N -di(4-methoxyphenyl) amino]-9, 9′-spirobifluorene (spiro-OMeTAD), was used as an additive for bulk heterojunction PSCs (BHJ-PSCs). The results showed that the PCE of mesoporous BHJ-PSCs (M-BHJ-PSCs) was enhanced by more than 15% when an extremely low concentration of spiro-OMeTAD additive was added. However, the crystallization of the perovskite was hampered and the recombination risk increased when grain boundaries increased in the perovskite layer. Planar BHJ-PSCs were fabricated to further investigate the role of additives. In comparison with those in planar BHJ-PSCs, the hole extraction efficiency and diffusion length significantly improved in M-BHJ-PSCs due to the transport paths and relay effects caused by the spiro-OMeTAD additive. Subsequently, exact functions and a new working principle of additives in BHJ-PSCs were proposed. This study may extend the possibilities of designing highly efficient PSCs through the promotion of additive research and application.